Keuntungan Bio-Ekonomi dan Lingkungan dari Energi Terbarukan: Tinjauan Komprehensif terhadap Praktik Terbaik - Mahdi; Sufitrayati; Syaifuddin Yana; Rita Nengsih; Filia Hanum; Susanti (Jurnal Serambi Engineering, 2024)
This literature study assesses the bio-economic and environmental advantages of renewable energy by doing a thorough examination of the most effective methods. Renewable energy technologies including solar, wind, and biomass power offer sustainable development with economic and environmental benefits, according to this report. Literature study, international case studies, and empirical data on renewable energy technology’ financial and environmental implications are employed. Long-term cost reductions, economic efficiency, local economic development, and bio-economy sustainability are highlighted in this article. Discussions include lower greenhouse gas emissions, enhanced air quality, ecosystem benefits, and natural resource conservation. The study found that renewable energy minimizes climate change and boosts local economies and industrial sustainability. Much current study focuses on environmental or economical concerns without considering their relationship. This article discusses how renewable energy strengthens the bio-economy and solves global economic and environmental problems. This study also suggests bio-economic policy changes and better implementation methods to optimize renewable energy benefits.